BIO-CHEMICAL MILIEU OF BUFFALOES OVARIAN FOLLICLES DURING THEIR DEVELOPMENT - LONE, A M; GUPTA, H P; PRASAD, SHIV; BAITHALU, R K (The Indian Journal of Animal Reproduction, 2023)
Biochemical constituents of ovarian follicular fluid were studied in relation to size of follicle in buffaloes. In thepresent study, ovaries were collected immediately after slaughter and the follicular fluid was aspirated and storedat-20°C. Sampling was done and were analysed for various biochemical constituents. Small follicle had significantlylower (P
Keywords: Buffalo; Ovarian follicular fluid; Biochemical milieu